A study on effect of silica fume and surface penetrant on bonding strength for overlaying - Shibao, Hayato; Mizan, Mahmudul Hasan; Ueda, Tamon; Miyaguchi, Katsuichi; Takahashi, Jun Takahashi (Journal of Asian Concrete Federation, 2019)
Currently, concrete structures are at risk of deteriorating conditions due to their exposure to various severe environments. Repairing and strengthening these structures is a better solution than replacing them by new constructions. As a retrofitting method, the top/bottom surface overlaying or jacketing method is commonly used around the world. In this method, polymer cement mortar (PCM) is sprayed/troweled onto the surfaces of concrete, and PCM adhesive strengthens the concrete structures. However, the concrete-PCM interface is considered to be the weakest part of a structure, and it may cause brittle fracture. This study focused on how this interface can be strengthened more effectively to prevent brittle fractures and investigated the effects of applying surface penetrant and silica fume from the perspective of chemical reactions. In addition, the reaction time relationship between PCM hydration and surface penetrant application time is also investigated based on a preliminary experiment. Mixing silica fume into PCM was conclusively found to strengthen the interface bonding strength in some conditions. Applying surface penetrant to an interface could decrease the interface strength if the application time was inappropriate. However, the results of an application time experiment indicated that it is possible to strengthen the interface via the surface penetrant.